Urgensi Pembubuhan Materai pada Salinan Akta Pejabat Pembuat Akta Tanah Sebagai Alat Bukti di Pengadilan Berdasarkan Undang-Undang Nomor 10 Tahun 2020 - Maryati, Maryati; Rostarum, Triamy; Puspita, Sri Ayu Indah (Universitas Batanghari Jambi, 2025)
The aim of this research is to identify and analyze the regulations for the use of stamps on copies of Land Deed Officials (PPAT) deeds as well as the validity of copies of PPAT deeds that use stamps as evidence in court. The research method used in this research uses a statutory approach so that the design of this research activity is for 6 months with the scope or object of this research, namely the urgency of recording stamp duty on Selena deeds of land deed officials as evidence in court. Where is the place of research, namely in the library with data collection techniques in the form of document study and analysis techniques, namely qualitative analysis. The results of this research are that regulations on the use of stamps on copies of PPAT deeds came into effect after the Stamp Duty Law was promulgated. Stamps function as formal requirements and evidence in court, not as an agreement. The absence of a stamp does not invalidate the legal action, but shows that the requirements as evidence have not been fulfilled and a copy of the PPAT Deed that uses a stamp is considered an authentic deed according to national land law, in accordance with Article 32 of Government Regulation Number 24 of 1997. However, even without a stamp, the legal action remains valid based on Article 1320 of the Civil Code. The seal functions as written evidence, and its absence does not result in the invalidity of the legal act, it only makes the agreement letter not fulfill certain requirements.